TNF-ALPHA: A RISK FACTOR FOR ISCHEMIC STROKE - Bokhari, Faraz Ahmed; Shakoori, Tania A.; Butt, Ambreen; Ghafoor, Farkhanda (Journal of Ayub Medical College Abbottabad, 2014)
Background: Inflammatory markers are being explored to aid in stroke diagnosis especially to differentiate between clinical varieties of stroke. This study aimed to compare plasma tumour necrosis factor-alpha (TNF-alpha) and Interleukin-10 (IL-10) levels between stroke patients and controls, as well as between hemorrhagic and ischemic varieties of stroke. Methods: Stroke patients who were admitted to Shaikh Zayed Hospital Lahore and Services Hospital Lahore, Pakistan within 24 hours after the onset of stroke symptoms were consecutively asked to participate in this study from June 2011 to December 2011.Venous blood samples were collected within 24 hours of stroke symptoms onset. Plasma TNF-Î± levels and IL-10 were calculated using commercial enzyme-linked immune-sorbent assay (ELISA). Cytokines levels were dichotomized as detectable yes/no and were compared between different groups using chi square test. Continuous variables were compared using the student t-test. Logistic regression model was used to investigate the effect of various risk factors on stroke subtypes. A value of p<0.05 was considered significant. Results: One hundred and thirty one stroke patients were included in the study, out of which 93 were ischemic and 38 were haemorrhagic stroke patients. Forty-seven healthy asymptomatic individuals were included as controls Plasma TNF-Î± levels (p<0.001, r=0.503, CI: 18.197-1672.950) were significantly elevated in stroke patients as compared to controls, along with advancing age (p=0.002, r=0.310, CI: 1.025-1.110) and history of hypertension (p=0.002, r=0.265, CI: 1.746-12.511). Males were found to be at a higher risk of developing stroke. Furthermore, history of hypertension (p=0.019, r= -0.294, CI: 0.134-1.500) and detectable TNF- levels (p=0.002, r=0.319, CI: 2.106-23.725) were found to be significantly different between ischemic and haemorrhagic stroke patients. Conclusion: TNF-Î± level differed highly significantly between stroke and controls, and also between ischemic and haemorrhagic stroke subtypes. Keywords: TNF-Î±, stroke, cytokines, inflammation, stroke, infarct, haemorrhage